A Comprehensive Review of the Main Lignan Components of Schisandra chinensis (North Wu Wei Zi) and Schisandra sphenanthera (South Wu Wei Zi) and the Lignan-Induced Drug-Drug Interactions Based on the Inhibition of Cytochrome P450 and P-Glycoprotein Activities - Zhang, Feng; Zhai, Jianxiu; Weng, Nan; Gao, Jie; Yin, Jun; Chen, Wansheng (Frontiers in Pharmacology, 2022)
Wu Wei Zi is the dried fruit of Schisandra chinensis (Turcz.) Baill. or Schisandra sphenanthera Rehd. et Wils. (family Magnoliaceae). As a homology of medicine and food, it has been widely used in China for thousands of years, to tonify the kidney, and ameliorate neurological, cardiovascular, liver, and gastrointestinal disorders. As its increasing health benefits and pharmacological value, many literatures have reported that the combination of Wu Wei Zi in patients has led to fluctuations in the blood level of the combined drug. Therefore, it is extremely important to evaluate its safety concern such as drug-drug interactions (DDIs) when patients are under the poly-therapeutic conditions. This review summarized the effects of Wu Wei Zi extract and its major lignan components on cytochrome P450 and P-glycoprotein activities, the change of which could induce metabolic DDIs. Our review also elaborated on the differences of the major lignan components of the two Schisandra species, as well as the absorption, distribution, metabolism, and elimination of the major lignans. In conclusion, these results would enhance our understanding of the DDI mechanisms involving Wu Wei Zi, and may potentially untangle some differing and conflicting results in the future.